ANALISIS PENYERAPAN TENAGA KERJA PADA USAHA TENUN DI KOTA DENPASAR TAHUN 2017 - Ratnasari, I Gusti Ayu Ratih; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2019)
The existence of a weaving business in the city of Denpasar is a potential in developing traditional fabrics with a variety of creativity and innovation that can not be separated from the demands of the market that continues to grow rapidly. This study aims to find out the absorption of labor in weaving businesses in the city of Denpasar, where weaving business potential in the city of Denpasar is able to compete with other businesses in the city of Denpasar to achieve better economic growth. The analysis technique used in this study is path analysis. The results showed variable capital, labor wages, and length of business had a positive and significant effect on the absorption of weaving business, while technology did not significantly influence the labor absorption of weaving businesses. Capital variables, labor wages, length of business, and technology do not affect the business output positively and significantly towards the weaving business output. Labor absorption is a variable that mediates the relationship between capital, labor wages, length of effort to output, while labor absorption does not mediate the relationship between technology and the output of weaving businesses in the city of Denpasar.